Catalytic Hydrogenation of Benzaldehyde on Ni/Al2O3 or Co-Ni/Al2O3 Catalyst - Liu, Wei; Li, Ying; Chen, Xianlan; Zhang, Pei; Yi, Ping; Zhou, Yongfu; Huang, Zhaolong (Asian Journal of Chemistry, 2012)
The Al2O3-supported Ni catalyst exhibits good activity for the catalytic hydrogenation of benzaldehyde. The activity and stability of the Ni/Al2O3 catalyst are affected by the amount of reductant, the conversion rate of Ni/Al2O3 and Co-Ni/Al2O3 catalyst achieving a maximum while the reductant is sufficient. Meanwhile, the reaction temperature and time show significant influence to the catalytic hydrogenation of benzaldehyde. The effect in catalytic hydrogenation of benzaldehyde on Co-Ni/Al2O3 catalyst is highest, it should be due to Co and Ni form to alloys and have the functional of the dual function catalyst, which is conducive to benzaldehyde was activated and forming benzyl alcohol. The conversion rate of benzaldehyde is close to 10.57 % while the reaction temperature reaches 80 ºC and time is about 2 h.